2014
DOI: 10.3354/meps10979
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance of the nektonic puerulus stage of spiny lobsters and implications of ocean warming

Abstract: Recent recruitment declines in important spiny lobster fisheries worldwide have triggered conjecture about negative impacts of anthropogenically induced environmental change on their long-lived planktonic larval life stages. Puerulus larvae are the critical transitional stage between pelagic larval development and coastal juvenile recruitment and may be particularly sensitive to environmental change due to immature cardiorespiratory capacity and exceptional energy demands associated with shoreward migration. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…However, it is noted that the regression slope of Ṁo 2 in hypoxia was slightly elevated for instar 16 phyllosoma compared to instar 9 phyllosoma and puerulus suggesting that this stage has the least respiratory control supporting the hypothesis of the study that late-phyllosoma would be most prone to oxygen limitation (Fitzgibbon et al, 2014b). This hypothesis is also supported by culture studies which show that the optimum temperature for late-stage phyllosoma growth and development (21°C) is reduced by 2°C compared to the early-and mid-stages and thermal optima for pueruli aerobic scope (15-27°C) far exceeds growth optima of all the phyllosoma stages (Fitzgibbon and Battaglene, 2012b;Fitzgibbon et al, 2014b). Further ontogenetic analysis of the physiological capacity is required to explain the apparent reduced thermal tolerance of late-stage phyllosoma and to confirm if it presents a thermally sensitive bottleneck in the lobster life cycle.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, it is noted that the regression slope of Ṁo 2 in hypoxia was slightly elevated for instar 16 phyllosoma compared to instar 9 phyllosoma and puerulus suggesting that this stage has the least respiratory control supporting the hypothesis of the study that late-phyllosoma would be most prone to oxygen limitation (Fitzgibbon et al, 2014b). This hypothesis is also supported by culture studies which show that the optimum temperature for late-stage phyllosoma growth and development (21°C) is reduced by 2°C compared to the early-and mid-stages and thermal optima for pueruli aerobic scope (15-27°C) far exceeds growth optima of all the phyllosoma stages (Fitzgibbon and Battaglene, 2012b;Fitzgibbon et al, 2014b). Further ontogenetic analysis of the physiological capacity is required to explain the apparent reduced thermal tolerance of late-stage phyllosoma and to confirm if it presents a thermally sensitive bottleneck in the lobster life cycle.…”
Section: Discussionmentioning
confidence: 86%
“…However, gobies naturally experience severe nocturnal hypoxia among the branches of coral colonies and are known to be among the most hypoxia tolerant of coral reef fishes (Sørensen et al, 2014). Little is known about the anaerobic capacity of phyllosoma but Fitzgibbon et al (2014b) showed that pueruli have significant anaerobic capacity most likely from within the tail white muscle fibres.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations